Pojedynek honorowy – demonstracja kompetencji honorowych czy pieniactwo? - Byczyński, Marcin (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Discussing the matter of dueling of honour a question always arises, is the duel of honour just another form of ritualized murder, an instrument to kill a person with full acceptance of the society, or is there something more about the duel of honour. Analyzing available historical sources and comparing different regulations from Polish codices of honour, the duel of honour will be scrutinized in search of its aim, of its grist, of its role in the honourable conduct. The competences demanded from a gentleman by the honour codices will be reconstructed answering the question – is the duel of honour a demonstration of certain competences or just barretry?